Program Ternak Domba Medal Saluyu sebagai Wujud Dukungan PLN Nusantara Power terhadap Pembangunan Energi Hijau - Rinda Primawarto; Aziz Bachtiar Cendekiawan; Muhammad Kivlan Hanin (Jurnal Syntax Admiration, 2024)
The Saluyu Medal Sheep Livestock Program shows significant progress and independence with the success of the livestock group in marketing products that are not only at the moment of qurbani but also able to develop a sustainable business model by processing sheep manure into fertilizer that is useful for agriculture in Karoya Village and for kaliandra trees in the PLN Nusantara Power UP Cirata Energy Forest Program. Not only that, through the implementation of this program, the leaves of kaliandra trees that previously had the potential to become waste are now used as sheep feed, which can reduce the risk of forest fires and support the principles of circular economy. This innovation not only increases the productivity and sustainability of the Karoya Village livestock business, but also contributes to environmental issues that support the development of green energy by reducing waste and utilizing resources efficiently within the framework of a circular economy.